Preaugmentation Soft Tissue Expansion: A Report of Four Pilot Cases - Farah Asa’ad; Gionata Bellucci; Luca Ferrantino; Davide Trisciuoglio; Silvio Taschieri; Massimo Del Fabbro (Case Reports in Dentistry)
This pilot study aimed at investigating the safety and feasibility of pre-augmentation soft tissue expansion (STE). Tissue expanders of different sizes (from 240 to 1300 mm3) were implanted subperiosteally in four patients requiring vertical and/or horizontal bone augmentation, and left in situ for 20–60 days, according to the expander size. Guided bone regeneration was carried out after STE completion. Horizontal and vertical bone gains were analyzed through CBCT. Optical scanning and superimposition of cast models were used for volumetric analysis. The mean soft tissue volume increase was 483.8 ± 251.7 mm3. Horizontal bone gain averaged 3 mm in two successfully expanded sites while one case had a vertical bone gain of 8 mm. Despite promising outcomes in bone and soft tissue gain, the present technique needs improvement before being applied routinely in everyday dental practice.